The Effect of Ground and Foliar Fertilization with Nitrogen, Phosphorus and Boron on Some Productive Indicators of Wheat Crop Sham 3 (Journal of Hama University, 2021)
The experiment was conducted on the farm of the College of Agriculture (Abu Jarash) during the agricultural season 2018/2019 in order to identify some productive indicators for the durum wheat crop Sham 3 when adding different levels of ground and foliar fertilizers with nitrogen, phosphorus and boron according to thirteen treatments and three replicates for each treatments, and add the fertilizer in some  treatments in two batches and others in one batch while foliar fertilizer was added in two stages: before flowering and after sitting fruit, and the physical and chemical properties of the soil and its content of N, P and B were determined before planting and adding fertilizer to them, the results showed that there were significant differences in some of the production indicators  of wheat crop among all treatment, compared to the control, and the best treatment is the fertilizing treatment No. (11) {75% NP ground (N batches + P two batches) +2% NP foliar + B foliar}Where it gave the highest values of plant weight (straw + grains) amounted to (2.65 kg.m 2) and the highest values of grain weight reached (530 g/m2), while the weight of a thousand grains reached its highest value (61.79 g).  Whereas the fertilizer treatment No. (10) {75% NP ground (N two batches + P one batch) +2% foliar NP + B foliar} was the best treatment for the number of spikes, as it reached (522.66) compared to the control and was significantly superior to the rest of the treatments . The other studies concluded that foliar fertilization as a supplement to ground fertilization is of greater importance for raising some of the productive indicators of wheat crop in calcareous soil conditions compared to ground fertilization alone.